COMPARASION OF LEVICA AND BUNASCAN IN SPINAL ANESTHESIA ACTION ON WORK ONCE AND SENSORIC BLOCKED IN ANALGESIA IN SECTIO CAESAREAN PATIENTS - Papo Lutfhie Chandra; Tophan Heri Wibowo; Mariah Ulfah (Bajang Institute, 2023)
The use of bunascan drugs was carried out when the Bontang Islamic Hospital was established, while the levica drug is still relatively new and has not been widely used in caesarean section surgery. This study aims to determine the comparison of levica with bunascan in spinal anesthesia on the onset of action and blockade of sensory analgesia in cesarean section patients at the Bontang Islamic Hospital. This research method uses a pre-experimental design with a type of one-shot case study. sampling technique with accidental sampling of as many as 78 respondents. The results showed that there was a significant difference between bunascan and levica on the onset of action and blockade of sensory analgesia, with a sensory block p-value of 0.007 and an onset of action p-value of 0.024. The average value of bunascan drugs is 62.9 seconds (sensory block) and 84.78 seconds (start of action), while levica is 87.3 seconds (sensory block) and 102.4 seconds (start of action). So the drug levica 15 mg has a sensory block of analgesia and a slower onset of action than bunascan 15 mg for spinal anesthesia in caesarean section.